Asymmetries of kinematics and kinetics in female and male sprinting - Nagahara, R.; Gleadhill, S. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: This study examined asymmetries in spatiotemporal (e.g. step length and frequency) and kinetic variables during maximal speed sprinting and aimed to determine differences in the asymmetries between female and male sprinters, and to examine relationships between magnitudes of asymmetries and sprint performance.